Eksistensi Pustakawan Sekolah Di Era Digital - Latifah Wahyuni (Institut Agama Islam Negeri Salatiga, 2019)
ABSTRACT In today's digital era, every activity of a person or organization is inseparable from sophisticated devices and the internet. The paperless era seems to have been implicated in every link of life including at school. At present many schools use devices and personal computers as the main tools for making various things related to learning activities such as school exam materials, daily assessments, and final semester assessments. The clearest example is the UNBK (Computer Based National Examination). The Ministry of Education has even distributed 1.75 million devices to a number of schools in order to expedite the school digitalization program called Rumah Belajar. The penetration of school digitalization has not yet been matched by the readiness of the school library and the ability of school librarians so that the school library and school librarian seem to be left behind and abandoned. Therefore, the author is interested in researching this matter. By using descriptive research methods the writer describes the existence of school library in the digital era and the existence of school librarians in the midst of the onslaught of information and technology. In order for school librarians not to be left behind and their existence to be calculated and needed in every sector, of course school librarians must upgrade themselves and transform into librarians who have the ability of technology, negotiation, collaboration and literacy.ABSTRAK Di era digital saat ini, setiap kegiatan dan aktifitas seseorang maupun organisasi tidak terlepas dari gawai canggih dan internet. Era tanpa kertas sepertinya telah menggejala di setiap lini kehidupan tak terkecuali di sekolah. Saat ini banyak sekolah yang menjadikan gawai dan personal computer untuk dapat membuat berbagai hal berkaitan dengan pembelajaran, materi ujian sekolah, penilaian harian, hingga Penilaian Akhir Semester (PAS). Contoh nyata yang paling jelas adalah UNBK (Ujian Nasional Berbasis Komputer). Bahkan kementrian pendidikan telah membagikan 1,75 juta gawai ke sejumlah sekolah guna memperlancar program digitalisasi sekolah yang bernama rumah belajar. Penetrasi digitalisasi ke sekolah ternyata belum diimbangi dengan kesiapan perpustakaan sekolah dan kemampuan pustakwan sekolah sehingga menjadikan perpustakaan sekolah dan pustakawan sekolah terkesan tertinggal dan ditinggalkan. Oleh karena itu penulis tertarik untuk meneliti ini. Dengan menggunakan metode penelitian desriptif penulis mengambarkan tentang keberadaan perpustakaan sekolah di era digital dan eksistensi pustakawan sekolah ditengah gempuran informasi dan teknologi. Dan agar pustakawan sekolah tidak tertinggal dan eksistensinya diperhitungkan dan dibutuhkan disetiap sektor, tentunya pustakawan sekolah harus mengupgrade diri dan bertransformasi menjadi pustakawan yang memiliki kemampuan teknologi, negosiasi, kolaborasi dan literate.